A sensitive and rapid chemiluminescence immunoassay for point-of-care testing (POCT) of copeptin in serum based on high-affinity monoclonal antibodies via cytokine-assisted immunization - Wang Y (Dove Medical Press, 2019)
Yu Wang,1 Emmanuel Enoch Dzakah,2,3 Ye Kang,1 Yanxue Cai,4 Peidian Wu,5 Bo Tang,5 Run Li,5 Xiaowei He11College of Food Science and Engineering, South China University of Technology, Guangzhou 510641, People’s Republic of China; 2Dermatology Hospital, Southern Medical University, Guangzhou 510091, People’s Republic of China; 3Department of Molecular Biology and Biotechnology, School of Biological Sciences, College of Agriculture and Natural Sciences, University of Cape Coast, Cape Coast, Ghana; 4School of Chemical Engineering and Energy Technology, Dongguan University of Technology, Dongguan 523808, People’s Republic of China; 5National & Local United Engineering Lab of Rapid Diagnostic Test, Guangzhou Wondfo Biotech Co., Ltd, Guangzhou 5l0663, People’s Republic of ChinaPurpose: Antibodies are key reagents in the development of immunoassay. We attempted to develop high-performance CPP immunoassays using high-affinity monoclonal antibodies prepared via cytokine-assisted immunization.Methods: We used fetal liver tyrosine kinase 3 ligand (Flt3L), CC subtype chemokine ligand 20 (CCL20), and granulocyte-macrophage colony-stimulating factor (GM-CSF) to assist traditional subcutaneous immunization of preparing high-affinity monoclonal antibodies, and further to develop high-performance immunoassay methods for CPP.Results: This novel immune strategy significantly enhanced immune response against CPP. Six anti-CPP monoclonal antibodies (mAbs) with high affinity were successfully screened and selected for application in a fully automated magnetic chemiluminescence immunoassay (CLIA). This robust and rapid assay can efficiently detect CPP in the range of 1.2–1250 pmol L–1, with a detection limit of 6.25 pmol L–1,. Significantly, the whole incubation process can be completed in 30 min as compared to about 4.5 hr for the control ELISA kit. Furthermore, this assay exhibited high sensitivity and specificity, low intra-assay and inter-assay coefficients of variation (CVs < 15%). The developed assay was applied in the detection of CPP in 115 random serum samples and results showed a high correlation with data obtained using a commercially available ELISA kit (correlation coefficient, 0.9737).Conclusion: Our assay could be applied in the point-of-care testing of CPP in the serum samples, and also the method developed in this study could be adopted to explore the detection and diagnosis of other biomarkers for various diseases.Keywords: copeptin, cytokine-assisted immunization, high-affinity antibodies, chemiluminescence immunoassay, point-of-care tests, clinical application